Influence of Food Choices, Shopping Routines, Food Handling, and Waste Prevention Behaviors on Food Waste Behavior in Bandung City - Kusumah, Adie Irwan; Dhameria, Vita; Setiawan, Iwan (Indonesian Journal of Business Analytics, 2024)
This research aims to examine the influence of food choices, shopping routines, food handling, and waste prevention behavior on food waste behavior in the city of Bandung. The population in the study were people who live in the city of Bandung and have thrown away food waste 3 times in the last month. The number of samples in this research was 50 respondents using convenience sampling techniques . The type of data used in this research is primary data collected using a survey approach via questionnaires distributed online with the time horizon used in this research being cross-sectional. This research uses analytical tools in the form of validity and reliability tests of instruments, classical assumption tests, hypothesis tests using multiple linear regression tests, and simultaneous tests. This research was assisted by statistical software program of social science (SPSS) version 26. Of the five proposed research hypotheses, all hypotheses are supported by empirical data. These findings indicate that food choices have a negative and significant effect on food waste behavior , shopping routines have a negative and significant effect on food waste behavior , food handling has a negative and significant effect on food waste behavior , and waste prevention behavior has a negative and significant effect on food waste behavior . This assessment also found that there is a simultaneous influence between food choices, shopping routines, food handling, and waste prevention behavior on food waste behavior.